Guidelines for Promoting the New Normal Professional Learning Communities in School: Guidelines for Promoting the New Normal Professional Learning Communities in School - Thipmanee, Phramaha Achirawitchyanan; Luechailam, Phramaha Tongsai; Sutajito, Phrakru Prariyatsutthikun (RATANABUTH JOURNAL, 2025)
This academic article aims to explore the guidelines for promoting professional learning communities (PLCs) in the context of the new normal within educational institutions. The findings reveal that the COVID-19 pandemic marked a significant turning point that accelerated the shift toward a new way of life and educational practices. Teachers were compelled to adjust their teaching and learning approaches to ensure educational continuity and effectiveness. In response, school administrators and educators must collaborate systematically as a network, emphasizing participation, shared learning, and continuous professional development. The integration of professional learning communities, supported by digital technology and modern communication platforms, serves as a vital mechanism for enhancing educational quality. This collaborative process enables knowledge sharing, peer reflection, and the cultivation of a sustainable learning organization, marking the beginning of a resilient and adaptive new-normal professional learning community within schools.